2009
DOI: 10.1128/iai.00158-09
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Specific Duffy Binding Protein Antibodies Correlate with Protection against Infection with Homologous Compared to Heterologous Plasmodium vivax Strains in Papua New Guinean Children

Abstract: Individuals repeatedly infected with malaria acquire protection from infection and disease; immunity is thought to be primarily antibody-mediated and directed to blood-stage infection. Merozoite surface proteins involved in the invasion of host erythrocytes are likely targets of protective antibodies. We hypothesized that Papua New Guinean children (n ‫؍‬ 206) who acquire high antibody levels to two Plasmodium vivax merozoite proteins, Duffy binding protein region II (PvDBPII) and the 19-kDa C-terminal region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
105
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 28 publications
6
105
2
5
Order By: Relevance
“…The full texts of these 162 studies were examined to determine whether they complied with eligibility criteria: 114 did not meet the inclusion criteria (see Additional file 3), 7 fulfilled the inclusion and quality criteria (Figure 1), and 41 studies potentially met inclusion and quality criteria. The authors of the 41 studies that potentially met inclusion and quality criteria were contacted, yielding a further 11 studies that met inclusion and quality criteria, providing a total of 18 studies that were included in the review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Figure 1). Details of these 18 studies are shown in Table 1.…”
Section: Identification and Description Of Included Studiesmentioning
confidence: 99%
“…The full texts of these 162 studies were examined to determine whether they complied with eligibility criteria: 114 did not meet the inclusion criteria (see Additional file 3), 7 fulfilled the inclusion and quality criteria (Figure 1), and 41 studies potentially met inclusion and quality criteria. The authors of the 41 studies that potentially met inclusion and quality criteria were contacted, yielding a further 11 studies that met inclusion and quality criteria, providing a total of 18 studies that were included in the review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Figure 1). Details of these 18 studies are shown in Table 1.…”
Section: Identification and Description Of Included Studiesmentioning
confidence: 99%
“…Antibody responses to PvDBP have been shown in endemic populations of P. vivax infection in Papua New Guinea, [23][24][25] Brazil, [26][27][28] and Colombia. 29 In addition, different studies suggested that stronger humoral and cellular immune responses to PvDBP-II develop progressively with increasing age, 22,24,29,30 showing a boosting effect that was likely because of repeated exposures to the infection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, antibodies that engage the dimer interface and/or receptor binding residues of DBL domains are potently neutralizing (9,18,19,31). Polymorphisms in DBP and the presence of multiple strains in endemic regions present unique challenges (32)(33)(34). Analysis of 676 bp within DBP-II revealed 127 polymorphic sites with nucleotide diversity varying between 0.006 and 0.0109, resulting in 193 haplotypes (35).…”
mentioning
confidence: 99%
“…Analysis of 676 bp within DBP-II revealed 127 polymorphic sites with nucleotide diversity varying between 0.006 and 0.0109, resulting in 193 haplotypes (35). These factors induce strain-specific protection rather than strain-transcending immunity, which leaves individuals susceptible to continued infection and disease (6,9,17,32,33,36).…”
mentioning
confidence: 99%